2008
DOI: 10.1016/j.cell.2008.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Reverse Transcriptase Delays Aging in Cancer-Resistant Mice

Abstract: Telomerase confers limitless proliferative potential to most human cells through its ability to elongate telomeres, the natural ends of chromosomes, which otherwise would undergo progressive attrition and eventually compromise cell viability. However, the role of telomerase in organismal aging has remained unaddressed, in part because of the cancer-promoting activity of telomerase. To circumvent this problem, we have constitutively expressed telomerase reverse transcriptase (TERT), one of the components of tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
307
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(325 citation statements)
references
References 62 publications
13
307
0
5
Order By: Relevance
“…The results also revealed prolonged telomere lengths of the Sca-1 + cells following Rg1 treatment. The results of the present study also demonstrated that high levels of telomerase activities were responsible for stem cell telomere maintenance, which was consistent with a previous report that telomere maintenance is the predominant mechanism underlying the anti-aging phenotype of telomerase-overexpressing transgenic mice (26).…”
supporting
confidence: 81%
“…The results also revealed prolonged telomere lengths of the Sca-1 + cells following Rg1 treatment. The results of the present study also demonstrated that high levels of telomerase activities were responsible for stem cell telomere maintenance, which was consistent with a previous report that telomere maintenance is the predominant mechanism underlying the anti-aging phenotype of telomerase-overexpressing transgenic mice (26).…”
supporting
confidence: 81%
“…Mice with transgenic Tert expression under the control of b-actin promoter also had increased incidence of spontaneous mammary tumors as they age . Coexpression of tumor suppressors p53, p16 and p19ARF in transgenic mice improved the fitness of epithelial barriers while attenuating the cancer-promoting effect of Tert (Tomas-Loba et al, 2008). Interestingly, tumor progression and dissemination by the constitutive expression of Tert was not dependent on telomere maintenance by telomerase as shown in Lck-Tert transgenic mice (Canela et al, 2004), suggesting that Tert per se may have a role in tumor progression and dissemination.…”
Section: Introductionmentioning
confidence: 70%
“…The activity of the telomerase enzyme complex responsible for maintaining the structure of the chromosome ends (telomeres) at each round of cell division likewise affects lifespan in a number of model organisms [11,12]. Still, the ageing process of postmitotic cells (like neurons) contradicts the theory.…”
Section: Introductionmentioning
confidence: 82%